Ultrasound-Faciliated Endovascular Fibrinolysis for Acute Bilateral Pulmonary Embolism in a Patient with SARS-CoV-2 Infection: Case Report - Al-Terki, Hani; Paulus, Tobias; Gotzmann, Michael; Mügge, Andreas (Cardiology and Cardiovascular Medicine, 2023)
A 73-year-old man was admitted with dyspnoea (NYHA III) and hypoxemia, making oxygen treatment necessary. The polymerase chain reaction (PCR) test was positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Echocardiography revealed a right heart dysfunction, a CT scan confirmed massive pulmonary embolism. Additionally, troponin and NTproBNP levels were elevated. According to the clinical findings and the elevated sPESI score, the patient was classified as intermediate–high risk. He was treated with heparin therapy as well as ultrasound-assisted, catheter-directed thrombolysis (USAT) over 6 hours. With this therapy, his vital parameters rapidly improved, oxygen therapy could be suspended, and the patient was transferred to the general ward the next day. Four days after admission, the patient was discharged under oral anticoagulation without any complaints.